Maksymilian Ryłło SJ (1802-1848) and the Beginnings of the New Catholic Mission in Africa in Nineteenth Century - Danieluk, Robert (Annales Missiologici Posnanienses, 2019)
The Polish Jesuit Maksymilian Ryłło (1802-1848) participated in several missionary endeavors undertaken by the Church in nineteenth century and entrusted to the Society of Jesus. Besides his missions in Middle East in 1836-1837 and 1839-1841, he was also one of the protagonists of an exploratory trip to North East Africa started in 1847 from Egypt and directed south. Arrived to Khartum and established there for a few months, Ryłło died in that city, while a few years later other missionaries took over the work of evangelization started by him and his companions. The present article introduces this Jesuit and focuses on the “African chapter” of his life – all as an attempt of filling the historiographical gap consisting in the fact that the English literature about Ryłło is almost inexistent.